Prevalence of Listeria monocytogenes and Listeria species and associated risk factors for contamination of milk and cottage cheese along the value chains in Ethiopia - Hassen, A.; Keba, Abdi; Ebrai, M.S.; Mamo, H.; Geleta, T.K.; Tessema, T.S.; Vipham, J.; Kovac, J.; Zewdu, A. (Elsevier, 2025)
This study aimed to comprehensively examine the prevalence of L. monocytogenes and Listeria spp. in dairy products including raw milk, pasteurized milk, and cottage cheese, and identify potential risk factors for contamination throughout the dairy value chain in major milk sheds in Ethiopia. We collected 912 samples, comprising 736 milk samples (368 raw and 368 pasteurized) and 176 cottage cheese samples, from the Oromia, SNNP, and Amhara regions. The isolation of L. monocytogenes and Listeria spp. followed the EN ISO 11290-1: 2017 standards, with confirmation via PCR targeting the lmo2234 and iap genes. The overall prevalence rates were 12.2 % for Listeria spp. and 4.7 % for L. monocytogenes. Notably, the prevalence of Listeria spp. (P = 0.024) and L. monocytogenes (P < 0.001) varied significantly across regions. Raw milk showed the highest prevalence of Listeria spp. at 15.2 %, followed by pasteurized milk at 12.2 %, and cottage cheese at 5.7 %, with these differences being statistically significant (P = 0.006). The prevalence of Listeria spp. differed significantly (P = 0.001) among the value chain stages (producers, collectors, processors, and retailers) and was 12.5 %, 17.9 %, 17.4 %, and 7.1 %, respectively. Furthermore, the prevalence rates in cottage cheese from producers and retailers were significantly different at 6.8 % and 4.5 % (P = 0.001). The prevalence of L. monocytogenes among milk producers, collectors, and processors was also significantly different, at 4.4 %, 5.4 %, and 12.0 % respectively (P < 0.001). Filtration of milk and cooling for preservation of milk were significantly associated with Listeria spp. or L. monocytogenes contamination at milk collectors' level (P < 0.05). These findings underscore the need for targeted interventions focused on the risk factors identified here to mitigate Listeria contamination in the dairy sector.